Matricellular proteins in cutaneous wound healing - Cárdenas-León, Claudia Griselda; Mäemets-Allas, Kristina; Klaas, Mariliis; Lagus, Heli; Kankuri, Esko; Jaks, Viljar (Frontiers in Cell and Developmental Biology, 2022)
Cutaneous wound healing is a complex process that encompasses alterations in all aspects of the skin including the extracellular matrix (ECM). ECM consist of large structural proteins such as collagens and elastin as well as smaller proteins with mainly regulative properties called matricellular proteins. Matricellular proteins bind to structural proteins and their functions include but are not limited to interaction with cell surface receptors, cytokines, or protease and evoking a cellular response. The signaling initiated by matricellular proteins modulates differentiation and proliferation of cells having an impact on the tissue regeneration. In this review we give an overview of the matricellular proteins that have been found to be involved in cutaneous wound healing and summarize the information known to date about their functions in this process.